2011
DOI: 10.1017/s1041610211001335
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of rapid cognitive decline in Alzheimer's disease: results from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of ageing

Abstract: Background:The AIBL study, which commenced in November 2006, is a two-center prospective study of a cohort of 1112 volunteers aged 60+. The cohort includes 211 patients meeting NINCDS-ADRDA criteria for Alzheimer's disease (AD) (180 probable and 31 possible). We aimed to identify factors associated with rapid cognitive decline over 18 months in this cohort of AD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
4
31
1
2
Order By: Relevance
“…The outcome for this group at 18 months has already been reported in detail (Sona et al, 2012), with rapid decline (greater than 5 MMSE points lost in 18 months) being predicted by baseline CDR (both total score and sum of box score) and the prescription of a cholinesterase inhibitor at baseline. The relationship between prescription of cholinesterase inhibitors and rapid cognitive decline has also been observed within the ADNI study cohort (Schneider, 2011).…”
Section: Discussionmentioning
confidence: 60%
“…The outcome for this group at 18 months has already been reported in detail (Sona et al, 2012), with rapid decline (greater than 5 MMSE points lost in 18 months) being predicted by baseline CDR (both total score and sum of box score) and the prescription of a cholinesterase inhibitor at baseline. The relationship between prescription of cholinesterase inhibitors and rapid cognitive decline has also been observed within the ADNI study cohort (Schneider, 2011).…”
Section: Discussionmentioning
confidence: 60%
“…Being female was associated with a 1.68-fold increase in the risk of any GDS score decline. Numerous previous studies 10,[34][35][36]39 have reported a similar impact of being female on risk of deterioration, although some research indicated that there was no significant relation between sex and disease progression. 40,41 This difference in disease progression between males and females may be due to hormonal differences, 42 as well as psychosocial issues associated with differing roles.…”
Section: Discussionmentioning
confidence: 94%
“…Individuals with rapid cognitive decline have a greater risk of falling and earlier loss of autonomy . To identify predictive factors of rapid cognitive decline, studies have analyzed the association between rapid cognitive decline and comorbidities, biological factors, and social conditions . Age, sex, education level, depression, malnutrition, neurological and psychiatric symptoms, AD stage, risk of falling, AD symptomatic treatment (cholinesterase inhibitors, N‐methyl‐D‐aspartate‐receptor antagonists, both), and degree of caregiver burden are predictive factors of rapid cognitive decline …”
mentioning
confidence: 99%